2013
DOI: 10.1038/nnano.2013.125
|View full text |Cite|
|
Sign up to set email alerts
|

Destructive extraction of phospholipids from Escherichia coli membranes by graphene nanosheets

Abstract: Understanding how nanomaterials interact with cell membranes is related to how they cause cytotoxicity and is therefore critical for designing safer biomedical applications. Recently, graphene (a two-dimensional nanomaterial) was shown to have antibacterial activity on Escherichia coli, but its underlying molecular mechanisms remain unknown. Here we show experimentally and theoretically that pristine graphene and graphene oxide nanosheets can induce the degradation of the inner and outer cell membranes of Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
1,221
5
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,332 publications
(1,282 citation statements)
references
References 48 publications
47
1,221
5
9
Order By: Relevance
“…They predicted that the lipid tails are parallel to the graphene surface ( Figure 6B). 57 This lipid extraction mechanism was used to explain the toxicity of graphene to bacterial cells. In other studies, lipid interaction was also proposed to be a major reason of the anti-microbial activity of graphene-based materials.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…They predicted that the lipid tails are parallel to the graphene surface ( Figure 6B). 57 This lipid extraction mechanism was used to explain the toxicity of graphene to bacterial cells. In other studies, lipid interaction was also proposed to be a major reason of the anti-microbial activity of graphene-based materials.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…So far, experimental methods can provide for these systems only limited information at the molecular scale level. For this reason, several simulation studies involving CNT and lipid bilayers have been reported [17,18,[21][22][23][24][25][26][27]. On the contrary, molecular dynamics simulations based on atomistic or coarse-grained models can provide detailed information on these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the insertion process of a small graphene nanosheet into a lipid bilayer structure has been studied using atomistic simulations [22].…”
Section: Introductionmentioning
confidence: 99%
“…The special features of the GO Nair et al, 2012;Lee et al, 2008;Hu et al, 2010;Tu et al, 2013;Lui et al, 2009;Novoselov et al, 2004;Dreyer et al, 2010;Hummers and Offeman, 1958;Drioli et al, 2015) make it to an excellent surface modification material. The GO surface modification can effectively exert the good separation properties of organic polymer active layer, and the chlorine resistance and anti-fouling properties of a GO layer simultaneously.…”
Section: Reasons For the Increase In Water Permeabilitymentioning
confidence: 99%
“…Water can nearly unimpeded permeated though graphene two-dimensional nanocapillaries (Nair et al, 2012). GO has other unique qualities, including ultrahigh strength (Lee et al, 2008), atomic-scale thickness (Novoselov et al, 2004), high antibacterial property and low cytotoxicity (Hu et al, 2010;Tu et al, 2013), and the possibility of producing ultraflat surface (Lui et al, 2009). It also possesses good chemical stability (Dreyer et al, 2010) and hydrophilic properties (Nair et al, 2012;Dreyer et al, 2010), and can be prepared from inexpensive graphite (Hu et al, 2010;Hummers and Offeman, 1958).…”
Section: Introductionmentioning
confidence: 99%